In-depth Analysis of Business Risks in the Cattle Livestock Industry: Comprehensive Literature Review - Jubaedah, Siti; Hilmi, Ihsan; Soares, Maria Ercia do Rosário Pereira Ximenes (Syntax Corporation Indonesia, 2024)
Cattle farming is a vital sector in the livestock industry, but it is also faced with various complex business risks. This literature review aims to provide an in-depth understanding of the risks associated with cattle farming. Through a thorough analysis of various literature sources, we explore the main aspects that influence risk in the cattle industry, including external factors such as fluctuations in feed prices, changes in government policies, and market uncertainty, as well as internal factors such as livestock health, financial management, and operational efficiency. By thoroughly understanding these risks, cattle farmers can develop effective mitigation strategies to increase the resilience of their business amidst the challenges facing the cattle farming industry.